Acanthamoeba castellanii interferes with adequate chlorine disinfection of multidrug-resistant Pseudomonas aeruginosa. Issue 3 (November 2020) - Sarink, M.J.; Pirzadian, J.; van Cappellen, W.A.; Tielens, A.G.M.; Verbon, A.; Severin, J.A.; van Hellemond, J.J.
Summary: Verona-Integron-encoded-Metallo-β-lactamase-positive Pseudomonas aeruginosa (VIM-PA) is a cause of hard-to-treat nosocomial infections, and can colonize hospital water networks alongside Acanthamoeba . We developed an in-vitro disinfection model to examine whether Acanthamoeba castellanii can harbour VIM-PA intracellularly, allowing VIM-PA to evade being killed by currently used hospital disinfectants. We observed that A. castellanii presence resulted in significantly increased survival of VIM-PA after exposure to chlorine for 30 s or for 2 min. This undesirable effect was not observed after disinfection by 70% alcohol or 24% acetic acid. Confocal microscopy confirmed the presence of VIM-PA within A. castellanii pseudocysts. Our data indicate that A. castellanii contributes to persistent VIM-PA colonization of water systems after chlorine treatment.